Children with moderate acute malnutrition have inflammation not explained by maternal reports of illness and clinical symptoms: a cross-sectional study in Burkina Faso. Issue 1 (December 2016) - Cichon, B.; Fabiansen, C.; Yaméogo, C.; Rytter, M.; Ritz, C.; Briend, A.; Christensen, V.; Michaelsen, K.; Oummani, R.; Filteau, S.; Ashorn, P.; Shepherd, S.; et al.
Abstract Background Morbidity plays an important role in the development of and recovery from malnutrition. Morbidity in children with moderate acute malnutrition (MAM) has not been described in detail and it is unclear how morbidity compares to serum levels of acute phase proteins (APPs) which indicate systemic inflammation and which can impede response to therapeutic nutritional interventions. The objective of this study was to describe morbidity in children with MAM and to assess to what extent maternally reported and clinically diagnosed morbidity explain the variation in APPs. Methods A cross-sectional sub study was conducted as part of a nutrition intervention trial among 6–23 months old children with MAM residing in Burkina Faso. Morbidity data collection at baseline included 2 week maternal recalls and physical examinations. Multivariate ANCOVA models were used to explore the associations between morbidity and C-reactive protein (CRP) as well as α1 -acid glycoprotein (AGP). These models were also used to determine to what extent morbidity explains variation in APPs. Results In the 2 weeks prior to the study inclusion visit, 38 % of children were ill according to mothers. Furthermore, 71.8 % of children had a symptom or infection identified during the physical examination and 24.2 and 66.4 % of children had elevated CRP and AGP, respectively. Among children without any identified symptom or illness at the inclusion visit, 10.7 and 46.5 % had elevated CRP and AGP, respectively. History of fever as well as nurse-documented fever, malaria, respiratory tract infections and skin infections were associated with higher levels of both APPs. History of cough and diarrhoea at the inclusion visit was associated with higher α1 -acid glycoprotein only. Overall, morbidity data only explained a small amount of the variation in APP levels (adjusted R2 below 0.2 in all tested models). Conclusion Morbidity among children with MAM in this setting is common, but maternal reports and clinical examination explained only a small proportion of the variation in APPs, indicating a presence of subclinical inflammation. We recommend further research into the causes of this subclinical inflammation as it could affect nutritional status and success of MAM treatment. Trial registration The trial was registered in the International Standard Randomised Controlled Trial Number Register (ISRCTN42569496 ).